Evaluation of the European Health Information Training Programme (EHITP): results from InfAct Joint Action - Verónica Gómez; Mafalda Sousa-Uva; Rita Roquette; Ana Cristina Garcia; Carlos Matias Dias (BMC, 2022)
Abstract Background The InfAct (Information for Action) is a Joint Action of the European Commission's 3rd Health Programme with the main goal to build an infrastructure of a health information system for a stronger European Union and to strengthen its core elements. The InfAct Joint Action was developed along 36 months and structured in 10 work packages. Portugal co-led the Work Package 6 (WP6) of this project, which included the development of the proposal of a flagship capacity building programme - the European Health Information Training Programme - and its evaluation. The evaluation objectives included: to evaluate the adequacy of the training programme to the health information needs in the European Member States; to identify possible changes regarding the participants selection process, the training activities and the pedagogical project; and to contribute to the understanding of the potential of the programme to add to available offers in learning on the topics of Public Health information, on the capacity building and behavioural changes in Public Health activities which can be attributed to the course, and of the potential of the programme to contribute to the alignment of health information criteria and procedures between the European Member States. Methods The evaluation process was developed using an observational descriptive study design using a mixed methodological approach with both document analysis and primary data collected by questionnaires and interviews analysis. Mixed quantitative and qualitative data collection methods and analysis were used. Results The proposal of the European Health Information Training Programme seemed adequate to the formative needs and capacities in line with the work performed by the InfAct project. In what concerns about its main thematic areas, it was also aligned with the areas identified in the previous formative needs and capacities mapping. The participants selection process proposed seemed, in general, adequate. The potential of the European Health Information Training Programme proposal to learning, capacity building and behavioral changes at work attributable to the course was considered positive, as well as the potential to the alignment of health information criteria and procedures between European Union Member States. Discussion In general, we found high consistency between the results obtained from data collected by the techniques used. However, different suggestions for improvement were outlined by the evaluation study population. Conclusions The proposed European Health Information Training Programme was a dynamic, flexible, sustainable formative programme in health information and focused on reducing inequalities.